PENERAPAN TEKNOLOGI PENCACAH DAUN DAN CAIRAN EM4 UNTUK MEMBUAT PUPUK KOMPOS MELALUI PENGABDIAN MASYARAKAT DI RT. 36, KELURAHAN KARANG JOANG KOTA BALIKPAPAN - Simamora, Gevbry; Habibie, Fadeli Muhammad; Syuhada, Subhan; Affandi, Bagus; Abdullo, Umar; Aghata, Rosi Pricilia; Afrianto, Rafli Dwi; Rachmadan, Rachmadan; Dewi, Siska Mulya (Jurnal Abdi Insani, 2024)
Agricultural fertilizers generally use chemical ingredients. Chemical fertilizers are relatively expensive, and their subsidized versions are becoming scarce. Therefore, the application of organic fertilizers can be an alternative to replace chemical fertilizers. The community of RT. 36 in Karang Joang Village is located in the Sungai Wein Protected Forest (HLSW) area, where there are many fallen leaves along the roads and in residents' yards. The residents in this area have expressed concerns about the cost of fertilizers for their agricultural needs. The aim of this activity is to help address this issue by providing a shredder to produce organic fertilizers. The activity began with a site survey, followed by community empowerment activities, which included the design and construction of a leaf shredder, socialization of tool usage and fertilizer production to the community, collection of fertilizer raw materials, and the production of organic fertilizer. The outcome of this community service activity is an increased understanding among the community of how to utilize dry leaves and the production of organic fertilizers that have been made and packaged for easy transportation and use. The conclusion drawn from this activity is that the goal of utilizing the leaf shredder to produce organic fertilizers has been achieved, thereby fulfilling the household agricultural needs in the surrounding area.